Lowering the Quality of Democracy by Lowering the Voting Age? Comparing the Impact of School, Classmates, and Parents on 15- to 18-Year-Olds' Political Interest and Turnout. Issue 4 (2nd October 2022) - Rossteutscher, Sigrid; Faas, Thorsten; Leininger, Arndt; Schäfer, Armin
ABSTRACT: Some scholars argue that lowering the voting age from 21 to 18 years led to declining turnout rates and increasing political inequality. Individuals in this age bracket are often no longer in school, frequently moved out from their parental home and are thus no longer within reach of the major political socialisation agents. We empirically test some of these claims and their effects on youngsters' political interest and turnout on a behavioural level. We use the 2017 state election in the German state of Schleswig-Holstein as our case, as the voting age had been lowered to 16 prior to this election. Thus, we are able to compare interest and turnout of those who are 16 and 17 years old with 'traditional' first-time voters at age 18. Our results show that lowering the voting age to 16 is unlikely to enfranchise a group of voters with an extraordinarily low propensity to turnout. It might in fact have a (relative) positive effect compared to slightly older voters, as more citizens at this age are still part of social networks that are conducive to electoral participation. At the same time, lowering the voting age might magnify existing inequalities because of network homogeneity.